Improving English teaching in Universitas Islam Indonesia: Implementation of cooperative learning - Dewi, Anita (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
Even though cooperative learning is quite a recent paradigm in the field of English teaching especially in English as a Foreign or Second Language (EFL/ESL) classes, it is actually not new for Indonesians. The concept, which relies on individual contributions upon communal achievement, is similar to the concept of gotong royong, which is undoubtedly an innate belief of Indonesians. The concept of gotong royong itself is frequently defined literally as mutual help. However, it is actually more than mutual help, since it also requires all society members’ participations in any event, for the sake of the community. This literature study is aimed at investigating the applicability of cooperative learning technique in the teaching of English in Universitas Islam Indonesia. The paper will be presented in the order of discussion on cooperative learning, followed by elaboration of gotong royong, and summed up by relevancies of the two concepts. It is possible that this technique also suits the teaching of other subjects, since the concept of cooperative learning and gotong royong would also facilitate the students in going into real life phenomena and experience. Nevertheless, the implementation of this method requires large scale and systemic changes to be ideal in nature.